Pengaruh Kepemimpinan dalam Meningkatkan Pelayanan Publik di Kelurahan Sitampae Kecamatan Tempe Kabupaten Wajo - Yusran Yusuf; Andi Supriadi; Burhanuddin Burhanuddin (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study aims to find out how much influence Leadership has in improving Public Services in  Sitampae Village, Tempe District, Wajo Regency. The background of this research is based on the importance of the influence of effective leadership in realizing quality, fast and targeted Public Services in the urban environment. In this context, leadership has a strategic role in directing, motivating, and supervising village officials to work professionally in accordance with their main duties and functions. The research method used is a quantitative approach with a census research type, where the entire population of 15 staff members is used as a staff Sample. The data collection techniques used are through questionnaires, observation and documentation. To analyze the data, descriptive analysis techniques and simple linear regression were used to test the Ha and Ho hypotheses. The results of the study show that Leadership has a significant influence in improving Public Services. This is evidenced by the results of data analysis which shows a determination coefficient value (R Squre) of 0.993, which means that 99.3% of the variation in Public Service can be explained by the Leadership variable. The rest, by 0.7%, was influenced by other factors not studied in this study. Thus, the hypothesis in this study can be accepted and concluded that the better the Leadership that is applied, the better the Public Services provided to the community.